1978
DOI: 10.1007/bf02034684
|View full text |Cite
|
Sign up to set email alerts
|

Induction of deoxyribonucleic acid degradation inEscherichia coli by ozone

Abstract: Cell survival and deoxyribonucleic acid (DNA) degradation wave measured for wild-type Escherichia coli B251 cells after exposure to different concentrations of ozone. The results show that extensive breakdown of DNA occurs after ozonation and that the extent of ozone-induced DNA degradation generally correlates with the colony-forming ability of the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Free radicals can cause damage to DNA, possibly by a scission of the sugar-phosphate backbone, producing strand breaks (Lesko et al, 1980;Brown & Fridovich, 1981;Simic & Jovanovic, 1986). Thus, 0, has, been shown to cause DNA single-strand breaks and/or doublestrand breaks in L929 fibroblasts (Ven der Zee et al, 1987a), wildtype Escherichia coli (Hamelin et al, 1978), calf thymus DNA (Ven Der Zee et al, 1987b), and alveolar macrophages (B,ermljdez et al 1991). Chromosome aberration and/or sister chromatid exchanges have been observed after an in vivo 0, exposure in the peripheral lymphocytes of animals (Zelac et al, 1971;Mckenzie et al, 1977) and humans (Merz et al, 1975;Guerrero et al, 1979).…”
mentioning
confidence: 95%
“…Free radicals can cause damage to DNA, possibly by a scission of the sugar-phosphate backbone, producing strand breaks (Lesko et al, 1980;Brown & Fridovich, 1981;Simic & Jovanovic, 1986). Thus, 0, has, been shown to cause DNA single-strand breaks and/or doublestrand breaks in L929 fibroblasts (Ven der Zee et al, 1987a), wildtype Escherichia coli (Hamelin et al, 1978), calf thymus DNA (Ven Der Zee et al, 1987b), and alveolar macrophages (B,ermljdez et al 1991). Chromosome aberration and/or sister chromatid exchanges have been observed after an in vivo 0, exposure in the peripheral lymphocytes of animals (Zelac et al, 1971;Mckenzie et al, 1977) and humans (Merz et al, 1975;Guerrero et al, 1979).…”
mentioning
confidence: 95%
“…DNA damage stimulates polyADP-ribosylatio n as an apparent requirement for DNA repair (Shall, 1984(Shall, , 1994Satoh & Lindahl, 1992;Malanga & Althaus, 1994), since the inhibitor of polyADPR synthetase greatly retards the DNA repair process (Cristóvâo & Rueff, 1996;Ménissier de Murcia et al, 1997;Trucco et al, 1998;Masutani et al, 1999). As mentioned in the introduction, a number of authors (Hamelin et al, 1978;Van der Zee et al, 1987a, 1987bRithidech et al, 1990;Görsdorf et al, 1990;Lee et al, 1995Lee et al, , 1996Ferng et al, 1997;Haney & Connor, 1999) have demonstrated that O 3 and NO 2 can cause DNA damage both in vitro and in vivo. In a previous publication (Bermúdez et al, 1999), we also demonstrated that ozone and nitrogen dioxide can cause DNA strand breaks in alveolar macrophages of rats exposed to similar conditions used in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…Also, in vivo exposure to NO 2 can induce mutations and chromosome aberrations in rat lung cells (Isomura et al, 1984). Exposure to O 3 has been shown to cause DNA single-strand breaks and double-strand breaks (Hamelin et al, 1978;Van der Zee et al, 1987a, 1987b. In vivo exposure to ozone increases DNA single-strand breaks in human and guinea pig lung cells (Lee et al, 1995).…”
mentioning
confidence: 97%
“…However, as the counts decreased (higher oxidant doses or longer contact times) a marked difference was observed between the metabolic activities after the two treatments: at the same microbial counts, the chlorine-treated culture exhibits higher respiratory activity (OUR and DHA a ) than that observed after applying ozone; therefore, ozone antimicrobial action was stronger. With regard to this, different studies on inactivation of E. coli with ozone indicated that lysis of the cells can result for high concentrations or extended ozone contact times (Perrich et al, 1975;Hamelin et al, 1978). Hunt and Mariñas (1999) indicated that noticeable changes in the interior of E. coli cells did not take place until most of the cells were non-viable, while subsequent exposure to ozone resulted in structural changes, membrane deterioration, and ultimately lysis of the inactivated cells.…”
Section: Analysis Of the Effect Of Ozone On Biomass Concentration In mentioning
confidence: 99%
“…Ishizaki et al (1987) suggested that ozone was able to diffuse through the cell membrane and react with bio-molecules and indicated that damage to chromosomal DNA might be one of the reasons for inactivation of E. coli. Other authors working with E. coli indicated that lysis of the inactivated cells can result after prolonged ozonation (Perrich et al, 1975;Hamelin et al, 1978;Hunt and Mariñas, 1999). White (1999) indicated that ozone disinfection is a direct result of cell wall disintegration and cell lysis.…”
Section: Introductionmentioning
confidence: 99%